Gas-Permeable Membrane Technology Coupled With Anaerobic Digestion for Swine Manure Treatment - Molinuevo-Salces, Beatriz; Riaño, Berta; Vanotti, Matías B.; García-González, María C. (Frontiers in Sustainable Food Systems, 2018)
This study was aimed at evaluating gas-permeable membrane technology (N-recovery) coupled with anaerobic digestion for the treatment of swine manure. For this purpose, 66.7% of the initial total ammoniacal nitrogen contained in centrifuged swine manure (SM) was first recovered by an e-PTFE gas-membrane as an ammonium sulfate solution. The resultant manure effluent with reduced ammonia (ATM) was evaluated as anaerobic digestion (AD) substrate. It was compared with AD using the initial swine effluent (SM) without the N-recovery step (control). An organic loading rate (OLR) of 2.8 ± 0.5 g TCOD L-1 day-1 was established to ensure a stable process when working at semi-continuous mode. Regardless of the operation mode, methane yields of 105 ± 2 mL CH4 g TCOD -1 were obtained for ATM. The combined treatment resulted in an organic matter removal efficiency of 68.6%. Initial TCOD accounted for 54.69 g L-1. The results prove that it is feasible to combine gas-permeable membrane technology and anaerobic digestion for the treatment of swine manure, contributing to ammonia emissions mitigation and sustainable livestock waste treatment. Moreover, by means of this technology combination, a variety of valuable products is obtained, namely sustainable energy in the form of methane and fertilizers.